MANAJEMEN PASIEN TUBERCULOSIS PARU - Devi Darliana (Fakultas Keperawatan-Universitas Syiah Kuala, 2011)
ABSTRACTThe incidens of tuberculosis is reported increased dramatically in the last decade in the wolrd includingIndonesia. Tuberculosis usually, develops in the developing countries or happens in the population with lowsocial economic. Tuberculosis is also one of the infectious diseases which caused the higher of mortality andmorbidity with prolong treatment. Patient can show a lot of symptoms for instance; productive cough, fever,night sweat, dyspneu, chest pain, anorexia and loss of body weight. The impacts of this disease not alsoinfluence of physical but also psychological. It also related with the higher of cost during hospitalized andrecovery at home. Therefore, it takes more responsibility with other professions such as physician, nurse, andanother health team to overcome this problem.Keywords: Management, increased intracranial pressure, stroke, brain tumor, patients